Selective Alkali Activation of Limestone for Additive Manufacturing in Construction: Influence of Alkali Concentration on Physical and Mechanical Properties - Mursaleen Shahid; Alexandre Pierre; Annelise Cousture; Vincenzo M. Sglavo (Applied Sciences)
Alkali-activated binders are gaining importance in the construction industry because of their environmental and mechanical advantages. This paper focuses on selective limestone activation (SLA) using aqueous sodium hydroxide solutions to be used as a non-hydraulic binder material. This study investigates the mechanical performance of 3D-printed specimens cured at 45 °C produced with different NaOH concentrations. Varying the NaOH concentration is significant for analyzing its role in optimizing the reactivity and mechanical behavior for additive manufacturing applications. The results show that mechanical strength and physical properties are influenced by the NaOH concentration, with the strength decreasing at higher sodium hydroxide loads. Although porosity and density are consistent in all concentrations, microstructure examination showed non-homogeneous grainy texture.